Chapter 7 Seeing double political polarization and identity politics in Macedonia, before and after the Prespa Agreement - Graan, Andrew (Taylor & Francis, 2021)
This chapter examines the emergence of two competing discursive and visual repertoires on Macedonian national identity in order to analyze and theorize contemporary political polarization as a new form of identity politics. Focusing on examples from the premiership of Nikola Gruevski and the 2018 referendum on the Prespa Agreement, the chapter describes how rival political movements developed distinct aesthetic forms to represent (North) Macedonia. On the one hand, Gruevski's nationalist political project embraced revivalist aesthetics to portray its version of the Macedonian nation and its history. On the other hand, critics of Gruevski drew from a modernist palette to represent their own version of a European and cosmopolitan Macedonia. Ultimately, in analyzing such "doubled" expressions of Macedonian identity, the chapter argues that the variety of political polarization evident in contemporary North Macedonia constitutes a new form of identity politics, one based not on multiculturalist claims to identity difference-so-called "recognition struggles"-but on competing, monopoly claims over one and the same identity category-characterized here as "representation struggles.